MORAL LAW AND JUSTICE IN DRUG ABUSE REHABILITATION - Siregar, Sutan; Padly, Fajar; Abidan, Abdul Aziz (PRANATA HUKUM, 2025)
Law as a social phenomenon is a reality of social life, or in other words, all forms of human relationships within society, whether they conform to human norms or rules of life or are prohibited, are described in law. Therefore, it can be said that what is established in law serves as a standard for governance and prohibitions in human life within society, aimed at creating a just, orderly, and prosperous life, thereby fostering a safe and happy existence. This situation can be seen specifically in the description of the national legal system, where the government of the Republic of Indonesia, since its independence, has sought to establish a national legal system to create a clean and authoritative state, so that the objectives of the Republic of Indonesia as stated in the 1945 Constitution 1945 Constitution to create a just and prosperous society, both materially and spiritually, will be achieved. The method used to analyze the problem will employ a descriptive research approach through library research and field research, utilizing data collection techniques such as interviews and document studies. Once the data is collected, it will be tested using deductive and inductive testing techniques. From the data generated in the research, it is evident that the factors causing criminal acts are to assist in committing criminal acts to obtain rewards in the form of goods or objects and/or destruction due to the intimate relationship with the perpetrator and/or revenge against the victim.